Genomes and virulence difference between two physiological races of Phytophthora nicotianae. Issue 1 (December 2016) - Liu, Hui; Ma, Xiao; Yu, Haiqin; Fang, Dunhuang; Li, Yongping; Wang, Xiao; Wang, Wen; Dong, Yang; Xiao, Bingguang
Abstract Background Black shank is a severe plant disease caused by the soil-borne pathogenPhytophthora nicotianae . Two physiological races ofP. nicotianae, races 0 and 1, are predominantly observed in cultivated tobacco fields around the world. Race 0 has been reported to be more aggressive, having a shorter incubation period, and causing worse root rot symptoms, while race 1 causes more severe necrosis. The molecular mechanisms underlying the difference in virulence between race 0 and 1 remain elusive. Findings We assembled and annotated the genomes ofP. nicotianae races 0 and 1, which were obtained by a combination of PacBio single-molecular real-time sequencing and second-generation sequencing (both HiSeq and MiSeq platforms). Gene family analysis revealed a highly expanded ATP-binding cassette transporter gene family inP. nicotianae . Specifically, more RxLR effector genes were found in the genome of race 0 than in that of race 1. In addition, RxLR effector genes were found to be mainly distributed in gene-sparse, repeat-rich regions of theP. nicotianae genome. Conclusions These results provide not only high quality reference genomes ofP. nicotianae, but also insights into the infection mechanisms ofP. nicotianae and its co-evolution with the host plant. They also reveal insights into the difference in virulence between the two physiological races.